Successful resolution of recurrent peritoneal dialysis-related peritonitis by listeria monocytogenes: a case presentation - Wu, Sharoui; Wu, Xiujuan; Yang, Yanru; Chen, Meili; Shen, Shuijuan (Journal of the Pakistan Medical Association, 2025)
Peritoneal dialysis-associated peritonitis caused by Listeria monocytogenes (LM) is a rare occurrence among peritoneal dialysis patients. It can be induced by an contaminated diet and lacks characteristic clinical manifestations. We present a case of recurrent peritonitis caused by LM. The patient an aged male, had a history of four years of peritoneal dialysis with diabetic kidney disease, high blood pressure, heart failure, chronic hepatitis B, and syphilis. The patient ingested food contaminated with monocyte listeria and had repeated symptoms of peritoneal cloudy, diarrhoea, abdominal pain, chills and fever. The efficacy of Cefazolin sodium combined with Ceftazidime is poor. Finally, its successful treatment included a combination of Vancomycin, Amikacin, and Piperacillin Tazobactam. Keywords: Listeria monocytogenes; Peritoneal dialysis; Peritonitis; Recrudescence.